2021
DOI: 10.1136/jclinpath-2020-207275
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid diagnostic modalities (fine needle aspiration and core needle biopsy) with histology correlation: a tertiary centre experience

Abstract: AimsTo determine the proportion of thyroid fine needle aspiration (FNA) and core needle biopsy (CNB) cases reported at a single institute into each UK Royal College of Pathologists (RCPath) Thy1-5 and local T category, respectively. Where subsequent histology was available, malignancy rates, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy were compared for both procedures.Methods1591 FNAs (2010–2018) and 514 CNBs (2013–2018) cases were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Core-needle biopsy (CNB), performed with a large bore spring-activated device, may provide a micro-histological sample from thyroid lesions. There are no clear advantages of using CNB, a more invasive and expensive procedure compared to FNA, based on cost and risk–benefit analysis ( 65 ).…”
Section: Thyroid Biopsymentioning
confidence: 99%
“…Core-needle biopsy (CNB), performed with a large bore spring-activated device, may provide a micro-histological sample from thyroid lesions. There are no clear advantages of using CNB, a more invasive and expensive procedure compared to FNA, based on cost and risk–benefit analysis ( 65 ).…”
Section: Thyroid Biopsymentioning
confidence: 99%
“…In recent years, core needle biopsy (CNB) from thyroid nodules has been recommended for previous inconclusive FNAs [ 21 ]. Also, some researchers have confirmed that CNB could overcome the limitations of FNA in these lesions [ 10 , 13 , 22 , 23 ]. However, the role of CNB has not been well established for the assessment of thyroid nodules with suspicious US features [ 10 ].…”
Section: Introductionmentioning
confidence: 98%